Algas perifíticas em um lago de planície de inundação : um estudo de longa duração, - Carapunarla, Luciana (2011)
This is the first approach of long-term research (11 years) about periphytic algae community in the Paraná River floodplain and is part of the LTER project - site 6. We sought to evaluate the structure of periphyton community in El Niño, La Niña and Normal periods, analyze abiotic factors influence on this structure and find a model to the density of periphyton algae community structure in the 11 years, correlating with Sea Surface Temperature Anomalies (SSTA) indicating the influence of El Niño or La Niña periods. The periphyton was collected in two anual periods (February or March and August or September), in the Patos Lake, High Paraná river floodplain`s lentic environment between 1999 to 2009. During eight years (1999 to 2001 and 2005 to 2009) was found higher values of density in August/ September and lower, in February/March. In other years (2002 to 2004) this pattern was reversed, with higher values in February/March months. In these years (2002 to 2004) the patterns of SSTA ranged, with La Niña and normality periods. The higher density was found in 2002 February, after a long drought. The lower density was found in 2005, in March this year, period with higher richness in the study (165 taxa), when the Paraná River level reached higher values. This year among all was recorded the highest abundance in August/ September periods. The total density pattern was determined by the diatoms (Bacillariophyceae) density variation, independent of hydrological period. In the eleven years the periphytic algae community density responded to local environmental variables, and the model summarized 45%of the first NMDS axis, indicating the community structure by water temperature, conductivity, alkalinity, nitrate and hydrometric level of the Paraná River. We conclude that the pulse characteristic (intensity, frequency and amplitude) was influenced by global climate phenomena (ENSO) influencing local environmental variables, which structure the periphytic algae community.